Preliminary result with incisional negative pressure wound therapy and pectoralis major muscle flap for median sternotomy wound infection in a high‐risk patient population. Issue 6 (13th September 2017) - Lo Torto, Federico; Monfrecola, Ambra; Kaciulyte, Juste; Ciudad, Pedro; Casella, Donato; Ribuffo, Diego; Carlesimo, Bruno
ABSTRACT: Deep sternal wound infection (DSWI) represents a dangerous complication that can follow open‐heart surgery with median sternotomy access. Muscle flaps, such as monolateral pectoralis major muscle flap (MPMF), represent the main choices for sternal wound coverage and infection control. Negative pressure incision management system has proven to be able to reduce the incidence of these wounds' complications. Prevena™ represents one of these incision management systems and we aimed to evaluate its benefits. A total of 78 patients with major risk factors that presented post‐sternotomy DSWI following cardiac surgery was selected. Thrity patients were treated with MPMF and Prevena™ (study group). Control group consisted of 48 patients treated with MPMF and conventional wound dressings. During the follow‐up period, 4 (13%) adverse events occurred in the study group, whereas 18 complications occurred (37·5%) in the control group. Surgical revision necessity and mean postoperative time spent in the intensive care unit were both higher in the control group. Our results evidenced Prevena™ system's ability in improving the outcome of DSWI surgical treatment with MPMF in a high‐risk patient population.